The internal and external consistency of a speech reception threshold test for isiZulu speakers with normal hearing sensitivity - Panday S; Kathard H; Pillay M; Wilson W (AOSIS, 2018)
Background and objectives: This study investigated reliability, particularly the internal and external consistency, of a new isiZulu speech reception threshold (SRT) test. Methods: To examine internal consistency, 21 adult isiZulu speakers with normal hearing sensitivity completed the SRT test using the first and second halves of the SRT wordlist in the same test session. To examine external consistency, a separate 23 adult isiZulu speakers with normal hearing sensitivity completed the SRT test, using the whole word list on two occasions 4 weeks apart. Consistency of SRT test scores in these test conditions was measured using intraclass correlation coefficient analyses (a measure of the consistency or reproducibility of different observations of the same quantity) and Bland and Altman analyses of agreement (a comparison of measurement error with the expected variation amongst subjects). Results: Intraclass correlation coefficient values ranged from 0.69 to 0.79, showing the isiZulu test scores were highly consistent between the test and retest conditions used in this study. Bland and Altman analyses showed that isiZulu speakers with normal hearing sensitivity can be expected to return isiZulu SRT test scores that differ by no more than 7.5 dB HL – 8.7 dB HL between original and repeat assessments. Conclusion: The isiZulu SRT test was reliable, showing high internal and external consistency, when used to assess first-language speakers of isiZulu with normal hearing sensitivity. These findings warrant continued development of the isiZulu SRT test for eventual clinical use. This development should include validating this test on first-language speakers of isiZulu with and without hearing loss.
(c) 2018 The Author/s
Keywords: Speech Reception Threshold; external consistency; internal consistency; split half reliability; test retest reliability; Adolescent; Adult; Female; Humans; Language; Male; Middle Aged; Reproducibility of Results; Speech Perception; Speech Reception Threshold Test; Young Adult